The North Atlantic Deep Western Boundary Current : seasonal cycle, decadal variability and relation to the Atlantic Meridional Overturning Circulation - Mielke, Charlotte Laura (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2014)
Despite its importance for the climate system, the natural variability of the Atlantic meridional overturning (AMOC) and its deep western return flow, the Deep Western Boundary Current (DWBC), is still not well understood. Observations of the AMOC or the DWBC exist at single latitudes and are usually limited to a few years, complicating the description of the seasonal cycle and the decadal variability. Also, it is not clear whether observations at one latitude are representative of the variability at other latitudes. Here, I first compare results from a high-resolution ocean model with observations of both scalar quantities and integrated transports to obtain the simulated DWBC. Second, I investigate the meridional coherence of the seasonal cycle and the decadal variability of the DWBC, and compare it to the AMOC's. I find that the DWBC has a robust seasonal cycle, which is closely related to the local wind stress curl variability. As a result, the DWBC shows a coherent seasonal cycle throughout both the subtropical and the subpolar gyre, but not across the gyre boundary. The modeled AMOC seasonal cycle, however, is coherent throughout the entire North Atlantic, but is 180-degree out-of-phase between the two available observational estimates. On decadal timescales, the DWBC's variability is also dominated by the local wind stress curl. This implies that the DWBC and the AMOC show opposing behavior if the western boundary and basin interior wind stress curl anomalies are of opposite sign. My results suggest that both the AMOC and the DWBC at one latitude are representative of the variability of the same quantity over a wide range of adjacent latitudes. AMOC and DWBC may -- under certain conditions -- be used as a proxy for one another: On seasonal timescales, the DWBC variability itself might be inferred from satellite observations, particularly in the subtropical North Atlantic. For an observational estimate of the seasonal AMOC variability, the thus-obtained DWBC would have to be combined with an estimate of ...